Fertiliser policies in ensuring food security and emerging issues in India - Singh, Bijay; Sapkota, Tek Bahadur (Fertiliser Association of India, 2025)
To ensure the sufficiency of food grains in the country, the Government of India has implemented several fertiliser policies since the 1950s to provide enough quality fertilisers to farmers at affordable prices. These policies influenced the consumption and balanced use of fertiliser nitrogen (N), phosphorus (P), and potassium (K) depending upon the soil, climate, cropping systems, and cultivated area under irrigation in different regions of the country. On all counts, accomplishment on the production of food grain front has paralleled the consumption of fertilisers since the 1960s. Even though the population of India increased more than three times from 1961 to 2022, per capita availability of rice remained almost the same and that of wheat increased by 3.1 times. In terms of the price of rice and wheat, affordability of urea has continuously increased since the introduction of the retention price scheme but that of P and K fertilisers remains an issue after the decontrol in 1992 for short-term, and implementation of nutrient-based subsidy policy in 2010. Imbalanced use of nutrients in some regions due to excessive application of highly subsidized N through urea or reduced application of expensive P and K fertilisers because of fertiliser policies led to economic losses as well as environmental and climate change hazards due to emission of nitrous oxide or nitrate leaching to water bodies. Foresight in fertiliser policy planning should address environmental and climate change consequences of fertiliser use and management but also ensures food security for the burgeoning population. Suitable policy mechanisms need to be evolved for gradually liberalizing urea while protecting the profits of farmers and affordability of fertilisers P and K should be ensured for the farmers.